Two new species of Paraxantia Liu & Kang (Tettigoniidae: Phaneropterinae; Vosiini) from Eastern Himalayas - Wu, Chao; Liu, Chun-Xiang (Zootaxa, 2021)
The genus Paraxantia Liu & Kang, 2009 hitherto included 8 species from China. Herein we describe two new species: P. rubripes sp. nov. from ES-Tibet and P. kaquewa sp. nov. from WN-Yunnan. A female of Paraxantia is described for the first time. The differences separating Paraxantia and Xantia are redefined. Illustrations and habitus images are provided. The distribution of Paraxantia species in China is discussed and mapped. The types are deposited in Insect Collection of Institute of Zoology, Chinese Academy of Sciences, Beijing, China (IZCAS).